Herança digital: desafios jurídicos e a escassez de regularização no Código Civil de 2002 - Favero, Kelen (2024)
This study discusses the need for the Brazilian Legal System to adapt to the new modalities of digital inheritance. As the development of technology is constant, and the environment virtual environment is increasingly present in personal relationships, legislation proves to be ineffective in keep up with the accelerated pace of current changes and their impacts. In a first part, it discusses briefly and summarized a history of the inheritance and its succession, following in a second section the which differentiates between intangible assets already recognized by the Civil Code of 2002 and digital images still without notes in the same Code. In the third stage, an analysis of the means found on digital platforms, in addition to examining ongoing bills and possible legal applications.